Descriptions of mature larvae and pupae of the genus Larinus (Coleoptera: Curculionidae, Lixinae) - Gosik, Rafał; Skuhrovec, Jiří (Zootaxa, 2011)
Descriptions of mature larvae of four species of the genus Larinus Dejean, 1821 are given: larvae of L. (Larinomesius) obtusus Gyllenhal, 1835 and L. (Phyllonomeus) turbinatus Gyllenhal, 1836 are described for the first time, and larvae of L. (s. str.) pollinis (Laicharting, 1781) and L. (Phyllonomeus) sturnus (Schaller, 1783) are described for the first time in detail. A revised identification key for the mature larvae and a new key for pupae are presented.